MENINGKATKAN HASIL BELAJAR LARI SAMBUNG DENGAN PENDEKATAN BERMAIN PUZZLE PADA SISWA KELAS V SD NEGERI KUPU 02 KEC. WANASARI KAB. BREBES TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study was to determine the increase in learning outcomes approach run continued with a puzzle in class V Elementary School District 02 Kupu Wanasari Brebes Academic Year 2012/2013. Techniques of data analysis done descriptively and through a predetermined formula counts. Research is successful if students achieve mastery and student learning outcomes from the first cycle to the second cycle.The results showed that the running game continued application of learning through play applications compiled puzzle, the fifth grade students of SD Negeri 02 Kupu Wanasari Brebes district. Student success in the first cycle of 68.97% (20 students completed; 9 students have completed the class average score 73.5) and the success of the second cycle of 100% (29 students finished with an average value of 83 classes) so that experienced increase from cycle I to cycle II of 31.03%.In connection with the above conclusion, that run continued learning provided by the teacher using a puzzle approach can improve the ability of the students continued running.